2007
DOI: 10.1007/s00445-007-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Miocene silicic volcanism in southwestern Idaho: geochronology, geochemistry, and evolution of the central Snake River Plain

Abstract: New 40 Ar-39 Ar geochronology, bulk rock geochemical data, and physical characteristics for representative stratigraphic sections of rhyolite ignimbrites and lavas from the west-central Snake River Plain (SRP) are combined to develop a coherent stratigraphic framework for Miocene silicic magmatism in this part of the Yellowstone 'hotspot track'. The magmatic record differs from that in areas to the west and east with regard to its unusually large extrusive volume, broad lateral scale, and extended duration. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
178
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(190 citation statements)
references
References 68 publications
11
178
0
Order By: Relevance
“…2) and comprises rhyolitic ignimbrites and thinner ashfall layers thought to be derived from eruptive sources concealed beneath basalts in the central Snake River Plain ). Prior to this study, it was subdivided into five members (Andrews and Branney 2005;Andrews et al 2008), with another 12 informal units ('BBU 1-12' of Bonnichsen et al 2008) reported on the adjacent Brown's Bench scarp (Fig. 1) of which two were correlated with units in the graben ).…”
Section: The Rogerson Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…2) and comprises rhyolitic ignimbrites and thinner ashfall layers thought to be derived from eruptive sources concealed beneath basalts in the central Snake River Plain ). Prior to this study, it was subdivided into five members (Andrews and Branney 2005;Andrews et al 2008), with another 12 informal units ('BBU 1-12' of Bonnichsen et al 2008) reported on the adjacent Brown's Bench scarp (Fig. 1) of which two were correlated with units in the graben ).…”
Section: The Rogerson Formationmentioning
confidence: 99%
“…2; 'BBU-2' of Bonnichsen et al 2008) is a crystal-poor (<2 %) intensely welded and rheomorphic rhyolitic ignimbrite, >20 m thick, exposed near the base of the Corral Creek section (Fig. 1).…”
Section: Corral Creek Membermentioning
confidence: 99%
“…Bonnichsen et al, 2008;Leeman & Lee, 2008!. These crystals formed in slowly cooling silica-rich magmas within crustal reservoirs.…”
Section: Samplesmentioning
confidence: 99%
“…1a). The thermal anomaly of the Yellowstone hotspot softened the lithosphere, triggering failure along planes with weak lithostatic strength and initiated rifting (Pierce and Morgan 1992;Wood and Clemens 2002;Bonnichsen et al 2004Bonnichsen et al , 2008. Rifting of the WSRP began at 12 Ma, correlating with the passage of the hotspot to the south and ceased at~7 Ma (Pierce and Morgan 1992;Wood and Clemens 2002;Bonnichsen et al 2004).…”
Section: Geological Overview Geological History and Settingmentioning
confidence: 99%
“…Associated with the initial rifting of the WSRP, between 11.7 and 11.0 Ma, localised rhyolite lavas, the BOwyhee Front volcanism^(the Jump Creek Rhyolite lava, the Reynolds Creek Rhyolite lava, the Cerro el Otoño Dome Field and the Wilson Creek Ignimbrite) were extruded from venting zones at the margins of the WSRP (Pierce and Morgan 1992;Perkins and Nash 2002;Bonnichsen et al 2004Bonnichsen et al , 2008Bonnichsen Walker and MacLeod (1991), Pierce and Morgan (1992), Cummings et al (2000) and Lewis et al (2012). Owyhee Mountains highlighted by box.…”
Section: Geological Overview Geological History and Settingmentioning
confidence: 99%